Homilies on the Psalms: Codex Monacensis Graecus 314 - Origenes 185-254 (The fathers of the church, 2020)
"In 2012 a previously unknown manuscript, containing 3rd-century writings, was discovered in a Munich library. Named Codex Monacensis Graecus 314, it contains 29 homilies in their original language, which is ancient Greek. Most of them had been previously unknown altogether, and a few had been known only in a subsequent Latin translation. Their author is the 3rd-century Christian theologian Origen (native of Alexandria, Egypt; died in Caesarea, Palestine). This book is the first English translation of these Greek homilies. In the homilies Origen provides interpretations of Psalms (of the Bible) -- interpretations that employ concepts of classical Greek theology and a three-level method of biblical interpretation (literal, moral, allegorical). He addresses questions about the goal of the Christian life, the church, the incarnation of Christ, and human nature"--